2014
DOI: 10.1016/j.jcrs.2014.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicities of moxifloxacin, cefuroxime, and levofloxacin to corneal endothelial cells in vitro

Abstract: Dr. Inoue is a medical advisor to Alcon Japan Ltd. No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Moxifloxacin also had direct toxic effects to other ocular cells. For example, corneal endothelial cells exposed to moxifloxacin caused cell damage with a reduction of intrinsic esterase activity 16 . An intracamerally injection of moxifloxacin can cause oxidative stress and caspase activation in corneal cells 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Moxifloxacin also had direct toxic effects to other ocular cells. For example, corneal endothelial cells exposed to moxifloxacin caused cell damage with a reduction of intrinsic esterase activity 16 . An intracamerally injection of moxifloxacin can cause oxidative stress and caspase activation in corneal cells 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Yoeruek et al 31 reported dose-dependent cefuroxime toxicity in cultured human corneal endothelial cells with toxicity observed in doses above 2.75 mg/mL. In another in vitro study, Haruki et al 32 found corneal damage at 24 hours in cefuroxime concentrations over 0.5mg/mL but not at 6 hours even at higher concentrations. Considering that aqueous humour is replenished at the rate of 1% per minute in a normal eye, for the standard dose of 1mg of ICC, the concentration of cefuroxime in the AC would decrease to 28% (0.76mg/mL) within 1 hour.…”
Section: Discussionmentioning
confidence: 99%
“…450 Several studies support the safety of intracameral moxifloxacin injection for endophthalmitis prophylaxis; 441,446,451 however, there is some evidence that higher concentrations may have a deleterious effect on the corneal endothelium. [452][453][454] Intracameral cefuroxime is available as a government-approved product in Europe, and moxifloxacin is commercially available in India. Because there is no FDA-approved product in the United States for endophthalmitis prophylaxis, moxifloxacin must be compounded for intracameral injection.…”
Section: P23mentioning
confidence: 99%